Kedudukan Sertifikat Merek Bagi Perlindungan Badan Usaha Mikro Kecil Dan Menengah - Pertiwi, Dian Eka; Tarina, Dwi Desi Yayi (JUSTISI, 2023)
Trademark registration which is one of the characteristics of msmes is often ignored by business actors. The increase in trademark registration is still not proportional to the number of existing msmes. The purpose of this research is to find out the status of a trademark certificate for the protection of Micro, Small and Medium Enterprises entities so that it supports the need for every Micro, Small and Medium Enterprises actor to immediately register their trademark in order to obtain protection under the applicable law. This study uses juridicial normative research by examining secondary legal materials supported by interview results as well as statutory approaches. The position of the brand certificate is important to provide legal protection for the registered trademarks of MSME actors. The government is making various efforts to continue to encourage msmes in terms of registering their trademarks such as holding a free trademark registration program to provide lower registration fees for msmes.